2019
DOI: 10.1111/trf.15407
|View full text |Cite
|
Sign up to set email alerts
|

Iron supplementation by blood donors: demographics, patterns of use, and motivation

Abstract: BACKGROUND: Iron supplements reduce the risk of iron depletion in blood donors. Recent initiatives have sought to increase use of donor iron supplementation (IS), but a baseline description of blood donor supplement practices is needed. STUDY DESIGN AND METHODS: Presenting blooddonors received a questionnaire inquiring about IS beginning in December 2015. Responses were linked to operational donor information and analyzed by multivariable statistics. ABBREVIATIONS: IS = iron supplementation; NHANES = NationalH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…One limitation of CHILL is that dietary iron consumption and use of multivitamins and iron supplements were not measured. One previous study found donors aged 17 to 25 were less than one-half as likely to report use of supplemental iron as older age groups (8% vs. 18%-30%), 26 a finding consistent with population-based surveys. 27 It may be that younger donors in CHILL were less likely to take iron supplementation, putting them at increased risk of NAID or IDA, and such behavioral differences might partly confound the reported associations with age.…”
Section: Discussionsupporting
confidence: 70%
“…One limitation of CHILL is that dietary iron consumption and use of multivitamins and iron supplements were not measured. One previous study found donors aged 17 to 25 were less than one-half as likely to report use of supplemental iron as older age groups (8% vs. 18%-30%), 26 a finding consistent with population-based surveys. 27 It may be that younger donors in CHILL were less likely to take iron supplementation, putting them at increased risk of NAID or IDA, and such behavioral differences might partly confound the reported associations with age.…”
Section: Discussionsupporting
confidence: 70%
“…The cross‐sectional data collection does not allow for identifiability of potential confounding by indication, and we did not elicit donor motivations for iron supplementation or gastric acid reducing medications. It is possible that some donors had recently initiated iron supplementation in response to blood center messaging, but available evidence indicates a large majority of donors either do not supplement with iron (80%) or report motivations for supplementation unrelated to blood donation (10%), suggesting negligible to modest impact . Finally, these findings do not address the clinical relevance of specific ferritin levels in the absence of anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Another reflection of the subjects' high commitment is their reported iron supplementation practices, both at baseline and in response to the LF letters. The proportion of platelet donors reporting iron supplementation surpassed 30% of those who provided information, far beyond the 21% of whole blood donors, from a recently reported study of one ARC region, who said they took iron regularly . Also, the survey findings that nearly two‐thirds of donors receiving the LF letter responded by taking iron both confirms donor willingness to take steps to maintain fitness for donation and suggests that ferritin testing can, within certain contexts at least, promote donor retention and stable platelet collections.…”
Section: Discussionmentioning
confidence: 91%
“…Platelet donations were grouped in increments of four procedures, which, based on our internal procedures, is roughly equivalent to one whole blood donation (estimated RBC loss for plateletpheresis with reinfusion is 54 mL). A brief, five‐question paper survey on iron supplementation practices was administered in participating regions during the study period, but completion was voluntary and not required for donation. The prevalence of LF, AIS, and associated risk factors were assessed at the first plateletpheresis visit tested for ferritin during the study period.…”
Section: Methodsmentioning
confidence: 99%